Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0306624x18764523
|View full text |Cite
|
Sign up to set email alerts
|

“Purely for You”: Inmates’ Perceptions of Prison Visitation by Volunteers in the Netherlands

Abstract: Research suggests that prison visitation by volunteers may significantly reduce the risk of recidivism. Community volunteers offer sustained, prosocial support to inmates which may account for these beneficial effects. However, the question of how inmates themselves evaluate volunteer visitation has hardly been studied. This study explores how inmates of Dutch prisons who receive one-on-one volunteer visits experience and value these visits. To that end, semistructured interviews were conducted with 21 inmates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Volunteers have an important effect on the inmates' attitudes, not only during their time in the prison, but also in the process of reintegrating inmates into society ( 9 – 11 ). Research conducted in Hong Kong ( 9 ) and the Netherlands ( 12 ) reported that volunteering in a prison context brings benefits not only to the volunteers, but also to the inmates themselves ( 9 , 12 ). A study in the United States of America (USA) highlighted that whilst volunteers had positive attitudes toward prisoners and prison staff, the beginning of these interactions was marked by some mistrust ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteers have an important effect on the inmates' attitudes, not only during their time in the prison, but also in the process of reintegrating inmates into society ( 9 – 11 ). Research conducted in Hong Kong ( 9 ) and the Netherlands ( 12 ) reported that volunteering in a prison context brings benefits not only to the volunteers, but also to the inmates themselves ( 9 , 12 ). A study in the United States of America (USA) highlighted that whilst volunteers had positive attitudes toward prisoners and prison staff, the beginning of these interactions was marked by some mistrust ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the results of a study in Australia ( 15 ), where medical students recognized the challenges and advantages of working in prison as a doctor, namely for the rejection of stereotypes. Studies carried out in Hong Kong ( 9 ), the Netherlands ( 12 ), Canada ( 16 ) and the USA ( 13 ) highlight that what led volunteers to become involved in prison volunteering contributed to the way they play their role as volunteer. The importance of visits made by volunteers, giving inmates opportunities to have different conversations and being away from the usual prison environment has also been highlighted ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the existing visitation research focuses on whether visits benefit adult inmates or not. However, a burgeoning body of literature has begun to explore the nuances and challenges of the visitation experience of adult inmates (Arditti & Few, 2008; Duwe & Clark, 2013; Schuhmann, Kuis, & Goossensen, 2018; Tasca, Mulvey, & Rodriguez, 2016). By and large, these studies find that visitation is hardly a uniform experience.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteers have an important effect on the inmates' attitudes, not only during their time in the prison, but also in the process of reintegrating inmates into society (9)(10)(11). Research conducted in Hong Kong (9) and the Netherlands (12) reported that volunteering in a prison context brings benefits not only to the volunteers, but also to the inmates themselves (9,12). A study in the United States of America (USA) highlighted that whilst volunteers had positive attitudes toward prisoners and prison staff, the beginning of these interactions was marked by some mistrust (13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in Hong Kong (9), the Netherlands (12), Canada (16) and the USA (13) highlight that what led volunteers to become involved in prison volunteering contributed to the way they play their role as volunteer. The importance of visits made by volunteers, giving inmates opportunities to have different conversations and being away from the usual prison environment has also been highlighted (12).…”
Section: Introductionmentioning
confidence: 99%